2019
DOI: 10.1101/799239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imprecise neural computations as source of human adaptive behavior in volatile environments

Abstract: Everyday life features uncertain and ever-changing situations. In such environments, optimal adaptive behavior requires higher-order inferential capabilities to grasp the volatility of external contingencies. These capabilities however involve complex and rapidly intractable computations, so that we poorly understand how humans develop efficient adaptive behaviors in such environments. Here we demonstrate this counterintuitive result: simple, low-level inferential processes involving imprecise computations con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Therefore, during testing, our artificial agents became observers bound to integrate the presented cues in the weather prediction task, whereas they remained agents seeking rewards through interaction with their environment in the bandit task 32,38 . Despite these fundamental differences, we found that computation noise promotes very similar functions during reasoning and meta-learning -two cognitive abilities associated with substantial computation noise in humans [18][19][20] .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Therefore, during testing, our artificial agents became observers bound to integrate the presented cues in the weather prediction task, whereas they remained agents seeking rewards through interaction with their environment in the bandit task 32,38 . Despite these fundamental differences, we found that computation noise promotes very similar functions during reasoning and meta-learning -two cognitive abilities associated with substantial computation noise in humans [18][19][20] .…”
Section: Discussionmentioning
confidence: 68%
“…The structure of the computation noise we implemented in artificial neural networks was directly inspired by these recent observations in humans [18][19][20] . But instead of relying on an 'algorithmic' description of underlying computations as in earlier work (Bayesian inference in the weather prediction task, reinforcement learning in the bandit task), we adopted a neural network description which offers several advantages 29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the context of fMRI investigations of value-based decisions, one may search for brain regions whose activity eventually perturbs the computation and/or comparison of options’ values. This would extend the portfolio of recent empirical studies of neural noise perturbations to learning-relevant computations (Drugowitsch et al, 2016; Findling et al, 2019; Wyart and Koechlin, 2016). Reciprocally, using some variant of mediation analysis (Brochard and Daunizeau, 2020; Lindquist, 2012; MacKinnon et al, 2007), one may extract neuroimaging estimates of neural noise that can inform DDM-based behavioral data analysis.…”
Section: Discussionmentioning
confidence: 92%